C–H and H–H bond activation via ligand dearomatization/rearomatization of a PN3P-rhodium(i) complex1. Issue 34 (14th September 2015) - Wang, Yuan; Zheng, Bin; Pan, Yupeng; Pan, Chengling; He, Lipeng; Huang, Kuo-Wei
<x xml:space="preserve">Abstract</x> A neutral complex PN3P-Rh(i)Cl (2) was prepared from a reaction of the PN3P pincer ligand (1) with [Rh(COD)Cl]2 (COD = 1, 5-cyclooctadiene).